Modified Pediatric ASPECTS Correlates with Infarct Volume in Childhood Arterial Ischemic Stroke - Beslow, Lauren A.; Vossough, Arastoo; Dahmoush, Hisham M.; Kessler, Sudha K.; Stainman, Rebecca; Favilla, Christopher G.; Wusthoff, Courtney J.; Zelonis, Sarah; Licht, Daniel J.; Ichord, Rebecca N.; Smith, Sabrina E. (Frontiers in Neurology, 2012)
Background and Purpose: Larger infarct volume as a percent of supratentorial brain volume (SBV) predicts poor outcome and hemorrhagic transformation in childhood arterial ischemic stroke (AIS). In perinatal AIS, higher scores on a modified pediatric version of the Alberta Stroke Program Early CT Score using acute MRI (modASPECTS) predict later seizure occurrence. The objectives were to establish the relationship of modASPECTS to infarct volume in perinatal and childhood AIS and to establish the interrater reliability of the score. Methods: We performed a cross sectional study of 31 neonates and 40 children identified from a tertiary care center stroke registry with supratentorial AIS and acute MRI with diffusion-weighted imaging (DWI) and T2 axial sequences. Infarct volume was expressed as a percent of SBV using computer-assisted manual segmentation tracings. ModASPECTS was performed on DWI by three independent raters. The modASPECTS were compared among raters and to infarct volume as a percent of SBV. Results: ModASPECTS correlated well with infarct volume. Spearman rank correlation coefficients (ρ) for the perinatal and childhood groups were 0.76, p<0.001 and 0.69, p<0.001, respectively. Excluding 1 perinatal and 2 childhood subjects with multifocal punctate ischemia without large or medium-sized vessel stroke, ρ for the perinatal and childhood groups were 0.87, p<0.001 and 0.80, p<0.001, respectively. The intraclass correlation coefficients for the three raters for the neonates and children were 0.93 [95% confidence interval (CI) 0.89-0.97, p<0.001] and 0.94 (95% CI 0.91-0.97, p<0.001) respectively. Conclusions: The modified pediatric ASPECTS on acute MRI can be used to estimate infarct volume as a percent of SBV with a high degree of validity and interrater reliability.